2023
DOI: 10.3390/jcs7020069
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Thermal Shock Response of Zirconia/304 Stainless Steel Functionally Graded Materials Fabricated by Centrifugal Slurry Methods

Abstract: Functionally graded materials (FGMs) are multi-phase composites with gradual spatial variations of constituents. The compositional transitions in the FGMs are classified into two manners such as continuous gradient manners and stepwise manners. In this study, zirconia (ZrO2)/ 304 stainless steel (SUS304) FGMs with continuous gradient manners were fabricated by a combination of centrifugal slurry methods and spark plasma sintering (SPS). A variety of continuous gradient patterns were achieved by controlling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The speed of the particles' sedimentation reduces as PCA is applied with higher amounts. Results from cyclic thermal shock tests showed that FGMs, 5-layered materials, and ZrO 2 single materials exhibited the strongest resistance among samples of FGMs with SUS304-rich continuous gradient patterns [20].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The speed of the particles' sedimentation reduces as PCA is applied with higher amounts. Results from cyclic thermal shock tests showed that FGMs, 5-layered materials, and ZrO 2 single materials exhibited the strongest resistance among samples of FGMs with SUS304-rich continuous gradient patterns [20].…”
Section: Introductionmentioning
confidence: 97%
“…Tsukamoto [20] has created continuous-gradient zirconia (ZrO 2 )/304 stainless steel (SUS304) FGMs using centrifugal slurry techniques and spark plasma sintering (SPS). He looked at several continuous gradient patterns made possible by adjusting the concentration of a dispersant like ammonium poly-carboxylic acid (PCA) in the slurry.…”
Section: Introductionmentioning
confidence: 99%